Vigabatrin Trials and Dose Recommendations - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2012)
Major, well-controlled trials of Vigabatrin for infantile spasms in Europe, Canada, and the Unites States are reviewed, including dose recommendations.